The Analysis of Melde Tool as Learning Media on Students Senior High School - Zul Jalal Hadi; Nazar Amrullah; Aruna Akbar Zhafransyah (Pancaran Pendidikan, 2020)
Physics is one of the subjects in high school taught by educators. However, in learning physical concepts are not only theoretically studied but in experiments or practicum. However, not all learning of physics concepts uses practice or experiment. This happens due to lack of facilities, time, and the low ability of teachers in making tools. Therefore the writer makes physics practice tools as learning tools and media namely Melde. The purpose of this discussion is as a medium of learning stationary wave material. The test results of making a melde tool on a stationary wave material are that the wave propagation speed on a rope depends on the length and weight of the load, the load mass relationship and the wave propagation speed are proportionally sincere, and the greater the load the greater the faster the propagation. Based on the results of testing the making of medle tool on stationary wave material it is suitable for use as a learning medium in schools.